Komodifikasi Hadis Hijrah dalam Akun Media Sosial Komunitas Kajian Musawarah - Rizaldi, Muh (Al-Bayan: Journal of Hadith Studies, 2023)
Hadiths on hijrah when presented in the form of content on social media have shifted their function from a religious basis to a commercial one. The Musawarah (Muda Sakinah Mawaddah Warahmah) study community account becomes an icon that draws the meaning of the hadith about hijrah to support the implementation of religious events and marketing of merchandise products sold. This paper intends to examine the phenomenon of commodification of hadith about hijrah in the social media accounts of the Musawarah study community. There are at least two questions raised in this article. 1) How is the discourse of hijrah hadiths in the social media accounts of the Musawarah Study community. 2) How are the forms of commodification of hijrah hadiths in the social media accounts of the Musawarah Study community. In answering these questions, this research will use the theory of the intersection of religion and media by Irwan Abdullah and Roland Barthes' semiotic theory. This study concludes that, the construction and distinction in the transmission of the meaning of the hijrah hadith becomes the basic foundation for the commodification of the hijrah hadith. At least three forms of commodification of the hijrah hadith were found. First, the commodification of hijrah hadith with the commercialization of hijrah fest event tickets. Second, the commodification of the hadith of hijrah with the commercialization of open sharia business stand services in the hijrah fest event. Third, the commodification of the hadith of hijrah by launching a sharia business with the narrative content of the hadith about hijrah. These three forms occur as a result of the process of symbolizing religion on social media which causes religion to no longer be imprissant in the human body but appears in lifestyle and entertainment codes that turn religion into a consumption process.